PROSES PENGAMBILAN KEPUTUSAN PEMBELIAN SAYURAN HIDROPONIK DI KOTA BANDAR LAMPUNG - Sutarni Sutarni; Luluk Irawati; Bina Unteawati; Clara Yolandika (Journal of Food System & Agribusiness, 2018)
The purpose of this study is to describe the decision making process of purchasing hydroponic vegetables. This research conducted in Bandar Lampung City. The study was conducted on 42 consumers of hydroponic vegetables and 42 non-hydroponic consumers. This research requires a qualitative method approach. Analysis of the stages of consumer purchasing decision-making process used to determine consumer behavior in making purchases of hydroponic and non hydroponic vegetables. Stages in the process of making consumer purchasing decisions in choosing commodities include the introduction of needs, information search, alternative evaluation, purchasing decisions, and post-purchase evaluation.Keywords: Decission Making, Hydroponic, Vegetable